2024
DOI: 10.3390/biomedicines12020407
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Auricular Vagus Nerve Stimulation to Improve Emotional State

Ainara Aranberri Ruiz

Abstract: Emotional experiences are a part of our lives. The maladaptive functioning of an individual’s emotional field can lead to emotional disturbances of various kinds, such as anxiety and depression. Currently, there is an increasing prevalence of emotional disorders that cause great human suffering and high socioeconomic costs. Emotional processing has a biological basis. The major neuroscientific theories of emotion are based on biological functioning, and all of them take into account the anatomy and function of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 131 publications
(209 reference statements)
0
0
0
Order By: Relevance
“…After a month of TENS use, fMRI revealed increased resting-state functional connectivity of the amygdala-lateral prefrontal network, which correlated with decreased scores of anxiety and depression [ 39 ]. Other studies have found that TENS, in addition to the amygdala, can modulate other cortical and subcortical structures such as the locus coeruleus, anterior cingulate cortex, and medial prefrontal cortex, which play a crucial role in the emotional regulation network [ 40 ]. However, decreased cortical activity in the somatosensory and motor cortices has been documented by EEG during both LF-TENS and HF-TENS [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…After a month of TENS use, fMRI revealed increased resting-state functional connectivity of the amygdala-lateral prefrontal network, which correlated with decreased scores of anxiety and depression [ 39 ]. Other studies have found that TENS, in addition to the amygdala, can modulate other cortical and subcortical structures such as the locus coeruleus, anterior cingulate cortex, and medial prefrontal cortex, which play a crucial role in the emotional regulation network [ 40 ]. However, decreased cortical activity in the somatosensory and motor cortices has been documented by EEG during both LF-TENS and HF-TENS [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%